Kl’Analisis Determinan Ekspor Gas Alam Indonesia dalam Periode 2000-2024 - Petrus Eko Widiyono; Zulfanetti Zulfanetti; Rosmeli Rosmeli (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the development of natural gas exports, investment, exchange rates, GDP, and natural gas export prices, as well as to analyze the effect of investment, exchange rates, GDP, and export prices on natural gas exports in Indonesia. This study uses descriptive and quantitative analysis methods. The data used are secondary data from 2000 to 2024. The data analysis technique used in this study is time series data analysis with a multiple linear regression econometric approach. The results of the study show that during the period 2000-2024, the average growth of natural gas exports decreased by -1.84 percent, while the average investment increased by 6,26 percent, the exchange rate by 2.58 percent, GDP by 8.61 percent, and export prices by 7,38 percent. The exchange rate variable has a significant negative effect on natural gas exports, while investment, GDP, and export prices have no significant effect on natural gas exports in Indonesia. Together, investment, exchange rate, GDP, and export prices have a significant effect on Indonesia's natural gas exports.